Demoting the Genetic Body: Part 3: The Human in the Body - Lock, Margaret (Anthropologica, 2022)
A summary of research findings about the "genetic body" revealed through genetic testing is followed by a discussion of the emerging science of epigenetics in which genes are understood as just one actor among many in the onset of disease. Current knowledge about the genetics of Alzheimer’s disease is set out and ethnographic data presented based on interviews with individuals who have been genetically tested for this disease. It is argued that genes will never be a powerful divinatory tool for the future in connection with common complex diseases such as Alzheimer’s.